The use of IAST for alcohol/water breakthrough separation simulations on all silica beta zeolite - Wittevrongel, Gille R.; Van Assche, Tom R. C.; Denayer, Joeri F. M. (Adsorption : journal of the International Adsorption Society, 2024)
This paper investigates the use of the Ideal Adsorbed Solution Theory (IAST) for alcohol/water breakthrough separation simulations on an all-silica beta zeolite. Because of its very hydrophobic nature, this zeolite presents peculiar isotherms for water and the alcohols, 2-methylpropan-1-ol, and ethanol. Isotherm fitting was performed using the Dual Langmuir-Sips (DLS) model for 2-methylpropan-1-ol and ethanol, while the Brunauer–Emmett–Teller (BET) model was chosen for water. To overcome the issues for evaluating the BET spreading pressure integral during IAST calculations, its isotherm at high partial pressures was limited to a capacity where its pore volume equals the pore volume occupied by ethanol and 2-methylpropan-1-ol. A 1D, trace, isothermal, axially dispersed plug flow model was employed to simulate and predict breakthrough curves for binary and ternary mixtures containing 2-methylpropan-1-ol, ethanol, and water. The IAST breakthrough separation simulations were validated with experimental data where both the equilibrium and dynamic behavior match well. This study concludes that IAST can be applied to alcohol/water mixtures when it is combined with a uniform and almost defect-free all-silica adsorbent.